CRIMINAL OFFENCE EXPLOITATION OF CHILDREN ECONOMICALLY AND SEXUALLY (Case Study Rule Number 86/Pid.Sus/2018/PN Pwt) - Mey Sylvia Loren; Shinta Rukmi Budiastuti; Endang Yuliana Susilowati (Wacana Hukum, 2021)
Humans, by nature, need protectin, even children. Society has an important place in the protection of children because of the increasing number of crimes that make children victims. One is the economic and sexual exploitation of children.The study is to review the judge's judgment of sentencing the childern  abuser to rule number 86/ pid. Sus /2018/ pn PWT.The study used a qualitative juridical analysis method. By data collection using literature related to research topics mainly secondary data supported from veridict, some books and regulations of legislation.The results of this study are the judicial judges' judgment of childern exploitation having already met elements that have established laws, evidence and exhibits but there is one element that does not fit the judge's theoretical faulty ruling. Yet, there is theoretically a flaw, which in the exercise of child abuse is a common misfit because a person is an instrument for a child doing a 15 - year - old sex work is sensible enough to understand consciously what the consequences are of his current and responsible work. The prosecution's low suit of punishment might influence the judge's ruling. The judge could prosecute higher and prosecution.